Fatigue behavior of lubricated Ni-Ti endodontic rotary instruments (Fracture and Structural Integrity, 2014)
The use of Ni-Ti alloys in the practice of endodontic comes from their important properties such as shape memory and superelasticity phenomena, good corrosion resistance and high compatibility with biological tissues. In the last twenty years a great variety of nickel-titanium rotary instruments, with various sections and taper, have been developed and marketed. Although they have many advantages and despite their increasing popularity, a major concern with the use of Ni-Ti rotary instruments is the possibility of unexpected failure in use due to several reasons: novice operator handling, presence manufacturing defects, fatigue etc. Recently, the use of an aqueous gel during experimental tests showed a longer duration of the instruments. The aim of the present work is to contribute to the study of the fracture behavior of these endodontic rotary instruments particularly assessing whether the use of the aqueous lubricant gel can extend their operative life stating its reasons. A finite element model (FEM) has been developed to support the experimental results. The results were rather contradictory, also because the Perspex (Poly-methyl methacrylate, PMMA) cannot simulate completely the dentin mechanical behavior; however the results highlight some interesting points which are discussed in the paper.
Keywords: Endodontic rotary instruments